2012
DOI: 10.4414/smw.2012.13520
|View full text |Cite
|
Sign up to set email alerts
|

Sun protective behaviour of primary and secondary school students in North-Western Switzerland

Abstract: In order to reduce the incidence of skin cancer in Switzerland, it is essential to improve children's and adolescents' sun protective behaviour. Future skin cancer prevention campaigns should teach proper use of sunscreen, and emphasise the value of wearing clothing and seeking shade as the most effective sun protection. Furthermore, major efforts are needed to change adolescents' attitude towards a suntan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
37
4
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 28 publications
12
37
4
5
Order By: Relevance
“…This prevalence was lower than that found in similar studies reported from Thailand (72.7%), 16 Australia (66.7%), 17 Italy (78.7%), 18 Brazil (74.3%), 19 and Switzerland (80.6%). 20 The percentage that we found was higher than that reported in only one study carried out in Singapore (22%). 21 We found no difference between sexes, although there was a female predominance in sunscreen usage in the literature.…”
Section: Discussioncontrasting
confidence: 81%
“…This prevalence was lower than that found in similar studies reported from Thailand (72.7%), 16 Australia (66.7%), 17 Italy (78.7%), 18 Brazil (74.3%), 19 and Switzerland (80.6%). 20 The percentage that we found was higher than that reported in only one study carried out in Singapore (22%). 21 We found no difference between sexes, although there was a female predominance in sunscreen usage in the literature.…”
Section: Discussioncontrasting
confidence: 81%
“…The students in groups A and B achieved progress in avoiding sun exposure and seeking shade at noon, but neither of the groups changed their use of sunscreens, hats, protective clothing, sunglasses, and sun umbrellas. This finding contradicted the finding reported by Reinau [5,6], in which > 95% of students benefited from the protection of sunscreen, but only 36% sought shade on sunny days.…”
Section: Discussioncontrasting
confidence: 85%
“…The U.S. Centers for Disease Control and Prevention recommends school programs on sun safety. Some school-based sun safety education programs have been reported in many studies, such as the "SunSmart Schools" in Victorian primary schools and other Australian states [4], a sun safety education program for primary school students in Switzerland [5,6], raising sun protection and early detection awareness among Florida high schoolers [7], and the SunWise Program in the US [8]. In Arizona, skin cancer prevention in the class education activity program, "Students are Sun Safe," was delivered by university students for middle and high school students [9].…”
Section: Introductionmentioning
confidence: 99%
“…Aus mehreren Studien geht hervor, dass Sonnenbrand und Hautkrebs als Folgen der UV-Strahlung sowie die Rolle von (1) Sonnenschutzmitteln, (2) Kleidung, (3) begrenztem Aufenthalt in der Sonne und (4) Meiden der Mittagsonne als protektive Maßnahmen den meisten Mitteleuropäern bekannt sind [19,20].…”
Section: Kenntnisstand Zum Thema Sonnenschutzunclassified